Beam control of high-power broad-area photonic crystal lasers using ladderlike groove structure. (8th May 2017) - Wang, Tao; Wang, Lijie; Shu, Shili; Tian, Sicong; Lu, Zefeng; Hou, Guanyu; Lu, Huanyu; Tong, Cunzhu; Wang, Lijun
Abstract: The high-power broad-area (BA) photonic bandgap crystal (PBC) diode laser is promising as a high-brightness laser source, however, it suffers from poor lateral beam quality owing to the intrinsic drawback of BA lasers. In this paper, a ladderlike groove structure (LLGS) was proposed to improve both the lateral beam quality and emission power of BA PBC lasers. An approximately 15.4% improvement in output power and 25.2% decrease in the lateral beam parameter product (BPP) were realized and the underlying mechanism was discussed. On the basis of the one-dimensional PBC epitaxial structure, a stable vertical far field was demonstrated.